Klasifikasi Buku Perpustakaan menggunakan Metode Naive Bayes - Risda Nur Ainum; Nurul Hidayat; Arief Andy Soebroto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Each library has book data that is stored and then developed to make it easier to classify the data Borong State Elementary School. This library stores book data that is managed. Data mining is for method that can be used is Naive Bayes where this method will be used to develop library books. This research is focused on knowing the library information system and classified in the category of types of books. From this classification, the system will provide information to students who will borrow books the categories available in the library. The input of this system is data regarding information. Variable used is type book that is often borrowed. Data mining technique algorithm tableas basis for book classification process. The input data will be processed using the data mining technique of the Naive Bayes Classifier (NBC) algorithm to form a probability tableas basis for the book classification process. In the form a library performance classification that predicts the of books and provides recommendations for the process of borrowing books in a timely manner. Factors classification library information are book publishers, book authors and year of publication. Library manager. Testing on library data 100% with a high level of accuracy category.